Tensile Properties for MWCNT Filled Jute-Epoxy Composites - Ahmad, Fauzan; Mohd Bakhori , Siti Nadia; Zuikafly, Siti Nur Fatin; Hassan, Mohamad Zaki (Journal of Advanced Research in Applied Mechanics, 2020)
This paper presents the tensile properties of jute-epoxy composite laminates with different weight percentage of multi-walled carbon nanotube (MWCNT). The jute fibre and epoxy resin that dispersed with MWCNT were used. The composite laminates were prepared by hand lay-up technique. Tensile test according to ASTM D3039 was carried out to obtain the tensile properties of the composite laminates. Three different weight percentages of MWCNT filled jute-epoxy were tested in this study. The experimental result found that the maximum tensile properties were recorded at 3% of MWCNT filler.